Understanding the Impact of Oven Temperature and Relative Humidity on the Beef Cooking Process - Dale R Woerner; Devin A. Gredell; J. Chance Brooks; J. D. Tatum; Jerrad F. Legako; Keith E. Belk; Lucas Arantes-Pereira; Nivaldo de Faria Sant’Ana; Robert J. Delmore (Meat and Muscle Biology, 2018)
The objective of this study was to evaluate the roles that cooking rate and relative humidity has on the sensory development of beef strip steaks. Thirty USDA Choice beef strip loins were collected from a commercial packing facility. Each strip loin was cut into steaks and randomly assigned to 1 of 6 cooking methods utilizing 2 oven temperatures (80°C and 204°C) and 3 levels of relative humidity [zero (ZH), mid (MH), and high (HH)]. Cooked steaks were used to evaluate internal and external color, Warner-Bratzler and slice shear force, total collagen content, protein denaturation, and trained sensory ratings. Relative humidity greatly reduced cooking rate, especially at 80°C. Steaks cooked at 80°C-ZH had the greatest (P < 0.01) cook loss of all treatments, and cook loss was not affected (P > 0.05). Steaks cooked at 80°C-ZH appeared the most (P < 0.01) well-done and had the darkest (P > 0.01) surface color. Total collagen was greatest (P < 0.01) in steaks cooked with ZH, regardless of oven temperature. Myosin denaturation was not affected (P > 0.05) by treatment. Increased (P = 0.02) sarcoplasmic protein denaturation was observed with ZH and MH, while increased (P = 0.02) actin denaturation was observed only with ZH. Oven temperature did not influence (P > 0.05) protein denaturation. Trained panelists rated steaks the most tender (P < 0.01) when cooked at 80°C and with ZH and MH. Humidity did not affect (P > 0.05) juiciness at 204°C; however, MH and HH produced a juicier (P < 0.01) steak when cooked at 80°C. Humidity hindered (P < 0.01) the development of beefy/brothy and brown/grilled flavors but increased (P = 0.01) metallic/bloody intensity. Lower oven temperatures and moderate levels of humidity could be utilized to maximize tenderness, while minimally affecting flavor development.